إثبات النسب في تأجير الأرحام في الفقه الاسلامي والقانون الجزائري - طويل اسماء (University of Eloued جامعة الوادي, 2024)
يعالج هذا البحث موضوع إثبات النسب في تأجير الأرحام ،الذي يعدّ من أهم مواضيع الساعة في الفقه الإسلامي والقانون الجزائري، وما يخلفه من مفاسد أسرية فيما يتعلق بحقوق هذا الطفل ؛ كحقه في النسب ،حيث أن نسب الطفل الناتج عن تأجير الأرحام فقد يكون من جهة أمه إلى الأم صاحبة البويضة؛ لأن المعيار البيولوجي هو المعيار الأساسي في النسب،أما من The research addresses the issue of proving lineage in surrogacy, which is considered one of the most important topics of the moment in Islamic jurisprudence and Algerian law, and the family harms it causes with regard to the rights of this child. Such as his right to lineage, as the lineage of the child resulting from surrogacy may be from his mother’s side to the mother who had the egg; Because the biological criterion is the basic criterion in lineage, as for paternity, we preferred to attribute this child to the father who had the sperm, due to the strength of the evidence, his saying.جهة الأبوة ،فقد رجحنا نسب هذا الطفل إلى الأب صاحب الحويمن الذكري.
Keywords: تأجير الارحام –الام البديلة –النسب; surrogacy - surrogate mother - lineage